Mergers and acquisitions in telecommunications market: a simultaneous equations approach to study Structure, Conduct and Performance - Antonios Kargas; Vasileios Argyroulis; Dimitrios Varoutas (International Telecommunications Society (ITS), 2023)
Paper aims to enrich readers understanding on Greek Telecommunication Industry, and more specifically on strategic decisions related with mergers and acquisitions. Even though mergers and acquisitions have long been studied in international level, the effects on market structure, on firms' conduct and, on their performance, remains an interesting topic. Current research contributes to the analysis of Greek telecommunication market, considering its current form, after a series of mergers and acquisitions that took place in previous years. An Industrial Organization's approach was adopted, namely the Structure - Conduct - Performance (SCP) framework. A SCP model, based on quantitative data, is developed for the major three telecom operators, while a two-stages least square regression analysis is conducted. By using a simultaneous equations model with lagged-dependent variables, the relationship between structure, conduct and performance is discussed. Results indicate that entry barriers exist in the market, as part of firms' conduct, shaping market's existing structure and affecting performance. Mergers and acquisitions is expected to keep playing a significant role in Greek telecommunications market since it acts as a reliable strategic option that ensures viability.
Keywords: 330; Structure – Conduct – Performance; Simultaneous equations approach; Mergers and Acquisitions; Strategic Management; Greek Telecommunications Industry